Association between common mental disorders and the severity of dysmenorrhea among female medical students at the University of Ibadan, Nigeria. - Yusuf Olatunji Bello; Oluwabunmi Victoria Adeyeye; Mary Mofiyinfoluwa Adeyeye; Olajumoke Aishat Oladosu; Oluwagbemisola Motunrayo Oderemi; Nasirat Ibukun Akinlade; Millicent Magdalene Maduka; Gloria Onyinyechi Madu; Victor Makanjuola; Jibril Abdulmalik; Imran Oludare Morhason-Bello (PLOS Global Public Health)
This study examines the association between common mental disorders, such as anxiety, depression, stress, and low self-esteem, and the severity of dysmenorrhea among female medical students at the University of Ibadan, Nigeria. This cross-sectional study was conducted among 171 female medical students that were menstruating regularly. Data were collected with a structured questionnaire validated by expert independent observer. Common mental disorders scores were computed using standardized assessment tools including GAD- 7 Anxiety Scale, Beck Depression Inventory, Perceived Stress Scale, and Rosenberg Self-Esteem Scale. The correlation coefficient was used to assess the relationship between each common mental disorder and the severity of dysmenorrhea. The Quantile-based G-computation (QGC) and Bayesian Kernel Machine Regression (BKMR) were used to evaluate both the relative and collective influence of the four common mental disorder scores on the severity of dysmenorrhea. There was a positive association between common mental disorders and severity of dysmenorrhea except self-esteem that was negatively associated. An increase of 1.17 (95% CI: 0.28 - 2.06) in the severity of dysmenorrhea per quartile difference was observed for the combined influence of the four common mental disorders. Anxiety had the highest relative influence on the severity of dysmenorrhea (weight: 0.36), followed by depression (weight: 0.31) and self-esteem (weight: 0.24). The collective influence of the four common mental disorders on the severity of dysmenorrhea was greater among participants with unsatisfactory relationships with their parents (β = 1.25) compared to those with satisfied relationships (β = 1.01). The study demonstrated a collective increase in the influence of the four common mental disorders on the severity of dysmenorrhea among female medical students.